IDENTIFIKASI TANAMAN OBAT UNTUK MENUNJANG KESEHATAN ANAK USIA DINI - Husnul Jannah; Sri Nopita Primawati (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Early childhood is a child in the age range of 0-6 years. At that time, there was a very high increase in children's development, and this was also a vulnerable period so that the need for deeper health services because children are susceptible to disease. Researchers found people in the City of Mataram, especially people in the District of Sekarbela, are still doing alternative medicine using some traditional medicinal plants to cope if their children experience illness or experience health problems. The purpose of this study are: 1) find out what health problems that are often experienced by early childhood in kindergarten Nurul Iman Sekarbela; and 2) to find out what traditional medicinal plants are given by parents when the child is experiencing health problems. This research includes quantitative descriptive research, which means studying the facts that occur by describing descriptions of traditional medicinal plants used by parents for early childhood health at TK Nurul Iman Sekarbela. The approach used in this research is a quantitative approach. The research sample was taken by purposive random sampling, namely children aged 5-6 years in kindergarten Nurul Iman Sekarbela. Data sources in this research are: 1) Nurul Iman Sekarbela Kindergarten; 2) the guardian of kindergarten students Nurul Iman Sekarbela; and 3) based on the results of discussions with the teacher and walid students obtained several types of diseases that are most often experienced are coughs, colds, and fever. Some types of plants that can and are commonly used by teachers and guardians of students include shallots, betel leaves, gambier, areca nut, lime, and betel leaves for the treatment of fever. Lime for the treatment of cough. Ginger and turmeric leaves for the treatment of colds and colds.